Declining fungal diversity in Arctic freshwaters along a permafrost thaw gradient. (30th August 2021) - Kluge, Mariana; Wauthy, Maxime; Clemmensen, Karina Engelbrecht; Wurzbacher, Christian; Hawkes, Jeffrey A.; Einarsdottir, Karolina; Rautio, Milla; Stenlid, Jan; Peura, Sari
Abstract: Climate change–driven permafrost thaw has a strong influence on pan‐Arctic regions, via, for example, the formation of thermokarst ponds. These ponds are hotspots of microbial carbon cycling and greenhouse gas production, and efforts have been put on disentangling the role of bacteria and archaea in recycling the increasing amounts of carbon arriving to the ponds from degrading watersheds. However, despite the well‐established role of fungi in carbon cycling in the terrestrial environments, the interactions between permafrost thaw and fungal communities in Arctic freshwaters have remained unknown. We integrated data from 60 ponds in Arctic hydro‐ecosystems, representing a gradient of permafrost integrity and spanning over five regions, namely Alaska, Greenland, Canada, Sweden, and Western Siberia. The results revealed that differences in pH and organic matter quality and availability were linked to distinct fungal community compositions and that a large fraction of the community represented unknown fungal phyla. Results display a 16%–19% decrease in fungal diversity, assessed by beta diversity, across ponds in landscapes with more degraded permafrost. At the same time, sites with similar carbon quality shared more species, aligning a shift in species composition with the quality and availability of terrestrial dissolved organic matter. We demonstrate that the degradation of permafrost has a strong negative impact on aquatic fungal diversity, likely via interactions with the carbon pool released from ancient deposits. This is expected to have implications for carbon cycling and climate feedback loops in the rapidly warming Arctic. Abstract : Thermokarst ponds are hotspots of carbon cycling in permafrost areas. Although the significant role of fungi in carbon cycling is well established for terrestrial environments, the role of aquatic fungi is still unknown. Our results show that permafrost thaw and related changes in carbon quality and quantity are tightly linked to a decrease in fungal diversity. In addition, the fungal community composition is clearly different in pristine and degraded permafrost sites, which do not share many OTUs. This suggests that permafrost thaw causes shifts in fungal communities, with unknown impacts on fungal metabolism and the landscape‐scale functioning of thermokarst ponds.